A preliminary study of diseases and insect plagues on bean collects in Mexico. - Muruaga Martínez, José S. (2016)
The INIFAP (Instituto Nacional de Investigaciones Forestales y Agropecuarias) herbarium specimens of Phaseolus spp. collected in Mexico during the period from 1978 to 1991 were examined with the aim of increasing our knowledge on the distribution of the insects and diseases that attack those species. A total of 775 specimens, including 24 different Phaseolus species from different regions of Mexico, were studied. Based on visual symptoms of pathogen damage, a wide geographic distribution of diseases and insects was observed in almost all species; most of them are the same pathogens that attack the cultivated common bean (P. vulgaris). It is possible to find genetic resistance to pathogens in the wild Phaseolus spp., resistance that may be useful to improve the cultivated forms in the genus. However, the utilization of germplasm of wild Phaseolus species will depend upon the thorough characterization of those species, their compatibility with the cultivated beans, and the inheritance of the traits involved.